Desenvolvimento social: lutas e contradições na atuação da rede de bibliotecas comunitárias Ilha literária - Freitas, Danielle Santos de (2022)
This papaperper aims to investigate the performance of the Community Library NetWork "Ilha Literária" in the context of the enforcement of the human right to reading in the Coroadinho and Cidade Operária neighborhoods, two peripheral communities of São Luís. The goal is to understand if and how these public spaces contribute to the social development of the communities where they are located. To critically understand this movement, our analyses were anchored in historical materialism as a methodological perspective. In relation to the theoretical referential that served as a basis and support for the development of this research, we prioritized authors who work with a critical-dialectical analysis of social reality, an indispensable process for the understanding of the object under study. Among the main references are: Karl Marx and Friedrich Engels, Antonio Gramsci, Jorge Acanda, Ricardo Antunes, Virgínia Fontes, Allyson Mascaro, Carlos Montano, among others. As instruments of data collection we used bibliographic research in the main research databases and documentary research in sources made available by the Literary Island NetWork. Field research was aided by notes in a field diary, the application of semi-structured interviews and the application of questionnaires. The results of the research indicate that even in the face of the advance of capital, community libraries resist and have been able to improve the lives of their audience and the community in which they are inserted through the humanizing application of reading. It is emphasized that the literature book, mediated from an emancipatory perspective, enables the discemment of Human Rights, stimulating the development of more conscious subjects, with abilities to better assimilate their responsibility in the world and to transform it through their conducts. Gramscian theory led us to identify that the main partners and subsidizers of the Literary Island NetWork form a conglomerate of Private Apparatuses of Hegemony that, together with others of differentiated scope and power, form a complex social network composed of a fraction of the Brazilian bourgeoisie, which acts on public education on several fronts, especially in the public policies of books and reading